2006
DOI: 10.1017/s0021849905050440
|View full text |Cite
|
Sign up to set email alerts
|

An IMC Approach to Event Marketing: The Effects of Sponsorship and Experience on Customer Attitudes

Abstract: The number of companies sponsoring events has increased over the past decade.Yet, for many firms it is unclear how the effectiveness of event marketing activities can be measured. The study examines outcomes associated with an automobile manufacturer's sponsorship of a six-day charitable sporting event. Data for the study were collected from a sample of 565 spectators in five cities during the six-day event.Results provide evidence for inclusion of event marketing in the company's promotional mix and indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 13 publications
1
71
0
10
Order By: Relevance
“…For example, Altunbas (2008) research about the event in the university has shown a direct positive effect of events on the brand awareness and product sales. On the other hand, it is revealed that event marketing's ability can affect positively perceptions and behavior (Sneath et al, 2005). Dregner et al (2008) propose that event marketing applications can be used to influence the brand image.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Altunbas (2008) research about the event in the university has shown a direct positive effect of events on the brand awareness and product sales. On the other hand, it is revealed that event marketing's ability can affect positively perceptions and behavior (Sneath et al, 2005). Dregner et al (2008) propose that event marketing applications can be used to influence the brand image.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Dregner et al (2008) propose that event marketing applications can be used to influence the brand image. Although, the effect of events on direct sales cannot be measured, it is understood from the responses that shortterm effects (Sneath et al, 2005). Likewise, it is stated that the events are important for companies to create environments in which customers will contact more with the product and brand.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Nowadays, more and more organizations sponsor big events such as the Oscars and the Super Bowl. They do this for marketing purposes and use social media to promote these events and their sponsorship (Sneath, Finney, Close, 2005;Thackeray et al, 2008). Similarly, Heineken created a major brand community by facilitating the Holland Heineken House during the Olympic Games to show the public what Heineken as a brand stands for (Holland Heineken House, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Desde esta perspectiva se ha planteado que el patrocinio, para ser realmente eficaz, debe ser considerado parte de una estrategia global de IMC (Integrated Marketing Communication) y no sólo una herramienta de comunicación aislada (Sneath et al, 2005).…”
Section: Introductionunclassified